Using Educative Curriculum Materials to Support the Development of Prospective Teachers’ Knowledge - Drake, Corey; Land, Tonia J.; Tyminski, Andrew M. (Educational Researcher, 2014)
Building on the work of Ball and Cohen and that of Davis and Krajcik, as well as more recent research related to teacher learning from and about curriculum materials, we seek to answer the question, How can prospective teachers (PTs) learn to read and use educative curriculum materials in ways that support them in acquiring the knowledge needed for teaching? We present two extended conceptual examples of ways in which educative curriculum materials might be used to support PTs in developing the knowledge needed for teaching. We follow these examples with a set of empirically based design principles and conclude with a brief consideration of unanswered questions related to the use of educative curriculum materials in teacher education.
Keywords: Mathematics Education; Qualitative research; curriculum; teacher education/development